The Open House Tradition to Strengthen Friendship In The City of Siantar From George Ritzer Perspective - Siddiq, Muhammad Abdillah; Nurlita, Fanni; Fitriani, Vira; Hutagalung , Syifa Azrina; Wati, Belna; Azmi, Reza Nur (GIC Proceeding, 2024)
An open house, in the context of Eid al-Fitr, is a cherished Muslim tradition where the doors of one’s home are figuratively opened to welcome family, relatives, neighbors, colleagues, and even the general public. During this festive occasion, guests are treated to a delightful array of foods and dishes while engaging in intimate conversations with the hosts. This time-honored practice, observed every Eid, serves as a powerful tool for fostering bonds of brotherhood and friendship. Through the act of opening one’s home, Eid al-Fitr embodies the spirit of renewal and forgiveness, signifying a fresh start and the beginning of a better chapter for all.